2014
DOI: 10.1177/2211068214547231
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Platform for Parallelized Cultivation and Monitoring of Microbial Growth Parameters in Microwell Plates

Abstract: The enormous variation possibilities of bioprocesses challenge process development to fix a commercial process with respect to costs and time. Although some cultivation systems and some devices for unit operations combine the latest technology on miniaturization, parallelization, and sensing, the degree of automation in upstream and downstream bioprocess development is still limited to single steps. We aim to face this challenge by an interdisciplinary approach to significantly shorten development times and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…In addition, substrate consumption or product formation can be efficiently determined using spectrophotometric MTP‐based assays . Here, the integration of MBR systems with liquid handling robots provides the possibility to sample microbial cultivations in an automated way …”
Section: Introductionmentioning
confidence: 99%
“…In addition, substrate consumption or product formation can be efficiently determined using spectrophotometric MTP‐based assays . Here, the integration of MBR systems with liquid handling robots provides the possibility to sample microbial cultivations in an automated way …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Knepper et al reported on robotic workflows for intermittent measurement of OD, pH and metabolites from cultures in 96-well plates in seven cycles at fixed times during 48 h cultivations [18]. Their successive sampling from plates incubated without humidity control led to a total volume reduction of 47% per well over 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose release experiments from polysaccharides are based on an EnPresso Y defined medium (from BioSilta, Cambridge, UK) (see ). The computerized platform with a Hamilton robot is introduced in .…”
Section: Methodsmentioning
confidence: 99%